Pengaruh Model Pembelajaran Project Based Learning Berbasis Etnosains Terhadap Hasil Belajar SBdP di SD Muhammadiyah Prabumulih - Muzdalifah, Asfa; Arafat, Yasir; Selegi, Susanti Faipri (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
The learning model is a learning structure that has been compiled, designed, and determined to achieve a desired learning goal. The background of this research is that students still lack knowledge about regional creative dances, and the low learning outcomes of students in regional creative dance material. To support ethnoscience-based learning, researchers use models Project Based Learning (PjBL) in the material of Cultural Arts and Crafts (SBdP) sub-material of regional dance creations. The population in this study were students of class IV, totaling 30 people. Sampling in this study was saturated sampling of 30 students. This study uses a quantitative experimental approach. Data collection was carried out by observation, interviews, written tests in the form of multiple choice and documentation. Data were analyzed usinguji paired t-test. Research design withpre-experimental design typeone group pretest-posttest (single group pre-test-post test). From the results of this study it can be concluded that the SBdP material (Cultural Arts and Crafts) sub-material for dance is based on ethnoscience using the model Project Based Learning (PjBL) is proven to have an influence on the learning outcomes of class IV students at Muhammadiyah Prabumulih Elementary School.